Gaze behavior in social interactions between beach volleyball players—An exploratory approach - Nicklas, Andre; Rückel, Lisa-Marie; Noël, Benjamin; Varga, Matyas; Kleinert, Jens; Boss, Martin; Klatt, Stefanie (Frontiers in Psychology, 2022)
In team sports, cooperative actions between players, coaches, and referees are essential in fostering teamwork and improving performance. Previous research has indicated that social interactions and gaze behaviour analysis in a group setting could be an important tool in accomplishing group objectives. However, only a few studies have examined the impact of social interactions on group dynamics in team sports and their influence on team performance. In this study, we investigate gaze behaviour in social interactions among beach volleyball players. We also analyse the influence of performance pressure on gaze behaviour within social interactions during a game. Furthermore, we assess whether higher game performance pressure could cause an increase in eye movements within the social action of the interaction between players and if these changes have an influence on the success of the subsequent rallies. Gaze behaviour of 18 expert beach volleyball players was analysed within their social interactions. Our results indicate that stress leads to more and longer fixation on teammates' faces. This research opens the door for more focused future work on the influence of social interaction within sports settings and their potential effects on athletes' performance.